Legal and economic aspects of VAT refund for travelers on the example of Polish-Belarusian border crossings (Discourse of Law and Administration, 2023)
The present article is aimed to determine the economic relevance of the VAT refundtool for travellers and whether the legal regulations in this area are optimal. The problem specifiedhere has an interdisciplinary character and constitutes an analysis of the relation of travellers’ exportto the export of Poland and its selected voivodeships (Podlaskie and Lubelskie Voivodeships) toBelarus in order to determine the significance of the phenomenon examined from an economic andlegal perspective. Based on this, the hypothesis was that the mechanism of VAT refunds to travellersbrings economic benefits, however, the construction of regulations and practice could be conduciveto abuse in this aspect. The methods used to verify the hypothesis were: dogmatic-legal, analysis ofliterature, regulations and case law, quantitative method, and structured interviews with employeesof the National Tax Administration and with entrepreneurs.
Keywords: tax free; vat refund for travelers; EU external border